Dissecting the Role of a Basic Helix-Loop-Helix Transcription Factor, SlbHLH22, Under Salt and Drought Stresses in Transgenic Solanum lycopersicum L. - Waseem, Muhammad; Rong, Xiangyi; Li, Zhengguo (Frontiers in Plant Science, 2019)
Environmental stresses, such as temperature, heavy metals, drought, cold, and microbial infections adversely damage various aspects of plant growth and development. Salinity and drought are among major hazardous factors, which adversity affects plant growth and productivity. Transcription factors, such as basic helix-loop-helix play critical roles in regulating plant physiological processes under abiotic stresses. In this study, we presented the characterization of a tomato SlbHLH22 gene under abiotic stresses such as drought and salinity. Plants overexpressing SlbHLH22 showed short height with small leaves and enhanced flavonoid accumulation. In wild type (WT) plant, the elevated levels of SlbHLH22 were detected under salt and D-mannitol stresses. Subcellular localization analysis revealed that SlbHLH22 protein was targeted to the nucleus in onion epidermal cells. Transactivation assay in yeast demonstrated that SlbHLH22 had transcriptional activation ability. The transgenic plants overexpressing SlbHLH22 displayed enhanced vigor and more tolerant to drought and salinity than WT. Overexpression of SlbHLH22 significantly peaked the activities of catalase (CAT), superoxide dismutase (SOD), and peroxidase (POD) to minimize the impacts of reactive oxygen species such as H2O2, which was reduced significantly in transgenic plants along with Malondialdehyde (MDA). Moreover, the expression levels of ROS defense genes (SlPOD, SlCAT, SlSOD), ABA biosynthesis genes, proline biosynthesis, and flavonoids synthesis genes were also activated under salinity and drought. Taken together, our study implies that the overexpression of SlbHLH22 improved tomato plant stress resistance by improving ROS scavenging system, increasing osmotic potential and enhanced accumulation of secondary metabolites in tomato plants.